2010
DOI: 10.1029/2009ja014851
|View full text |Cite
|
Sign up to set email alerts
|

Sprite discharges on Venus and Jupiter‐like planets: A laboratory investigation

Abstract: [1] Large sprite discharges at high atmospheric altitudes have been found to be physically similar to small streamer discharges in air at sea level density. Based on this understanding, we investigate possible sprite discharges on Venus or Jupiter-like planets through laboratory experiments on streamers in appropriate CO 2 -N 2 and H 2 -He mixtures. First, the scaling laws are experimentally confirmed by varying the density of the planetary gasses. Then, streamer diameters, velocities, and overall morphology a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 63 publications
3
47
0
Order By: Relevance
“…The presence of this ionizing radiation with significant penetration length in air was demonstrated in numerous experiments [18]. A similar mechanism was proposed by Dubrovin et al in section 2.2 of [16] for the H 2 :He mixtures on Jupiter-like planets; she argues that there are electronically excited He states that can emit photons with sufficient energy to ionize H 2 while no such mechanism exists for Venus (CO 2 :N 2 ). However, the only quantitative photo-ionization model exists for the moment, to our best knowledge, for N 2 :O 2 mixtures like air [19].…”
Section: Photo-ionizationmentioning
confidence: 81%
See 2 more Smart Citations
“…The presence of this ionizing radiation with significant penetration length in air was demonstrated in numerous experiments [18]. A similar mechanism was proposed by Dubrovin et al in section 2.2 of [16] for the H 2 :He mixtures on Jupiter-like planets; she argues that there are electronically excited He states that can emit photons with sufficient energy to ionize H 2 while no such mechanism exists for Venus (CO 2 :N 2 ). However, the only quantitative photo-ionization model exists for the moment, to our best knowledge, for N 2 :O 2 mixtures like air [19].…”
Section: Photo-ionizationmentioning
confidence: 81%
“…While most work focusses on positive streamers in air, positive streamers have been observed in varying nitrogen:oxygen ratios [11,12,13,14], in argon [15] as well as in gas mixtures presenting the atmospheres of Venus (CO 2 :N 2 ) and of Jupiter-like gas giants (H 2 :He) [16]. In a recent experiment [14], positive streamers were observed in nitrogen, oxygen and argon with impurity levels below 1 ppm; they propagate with essentially the same velocity as in air, but are thinner and less straight, they branch more, move more in a zigzag fashion or even can form feathery structures.…”
Section: Positive Streamers In Varying Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated S(λ) by measuring the spectrum of a streamer and glow discharge at low pressures (50 to 200 mbar, Figure A1). The spectrum was recorded using three small Ocean Optics spectrometers together spanning the wavelength range of 230-940 nm, at several pressures and voltages, similarly to Dubrovin et al [50]. This spectrum is similar to measured and calculated sprite and streamer spectra (see e.g.…”
Section: Appendix a Description Of Camera Calibrationmentioning
confidence: 91%
“…In the Venus atmosphere hardly any streamers were observed, at the most a single one was seen at the front of the propagating leader. Dubrovin et al [2010] also found that streamers are very difficult to produce in a Venus Atmosphere above 0.8 bar (608 torr). These observations suggest that in high-pressure gases containing CO 2 the streamers do not play a significant role in the propagation of the discharge.…”
Section: Discussionmentioning
confidence: 99%